Racial differences in α4β7 expression on CD4+ T cells of HIV-negative men and women who inject drugs - Martin, Alyssa R.; Sivro, Aida; Packman, Zoe R.; Patel, Eshan U.; Goes, Livia R.; McKinnon, Lyle R.; Astemborski, Jacquie; Kirk, Gregory D.; Mehta, Shruti H.; Cicala, Claudia; Arthos, James; Redd, Andrew D.; et al. (PloS one, 2020)
We performed a cross-sectional study of HIV-uninfected men and women who inject drugs from the ALIVE cohort to examine if black men and women who inject drugs have higher levels of CD4+ T cells expressing the integrin heterodimer α4β7 compared to white men and women. Flow cytometry was used to examine expression of α4β7 and other markers associated with different functional CD4+ T cell subsets in both men and women who inject drugs. Higher levels of α4β7, CCR5, and CCR6 were observed on CD4+ T cells from black participants compared with white participants. In a multivariable model, α4β7 expression differed by race, but not sex, age, or other factors. Black men and women express higher percentages of α4β7 expressing CD4+ T cells, which may play a role in HIV disease.